The opium problem in Turkey, 1930-1945 - Gürsoy, Özgür Burçak. (Thesis (M.A.)-Bogazici University. Atatürk Institute for Modern Turkish History, 2007., 2007)
This study examines the opium problem in the early Republican Turkey with its political, economic and social aspects. Opium, as an agricultural commodity, conceptually transformed under the hegemony of modernscientific medical discourse with the turn of the twentieth century, and became one that had to be economically, politically and legally restricted and controlled at both international and national levels. Turkey took part in this global change more in the 1930s. The opium was taken under the state monopoly by the new laws issued in 1933 for Turkey’s participation to the international conventions on opium, and by the enactment of these laws, its cultivation was limited, and its foreign trade was regulated and restricted. However, this process was quite tense for a country like Turkey, which was one of the most significant highquality opium producers of the world, and this tension created an “opium problem” for all related actors until World War II. The war conditions both weakened the international control of the opium trafficking and increased the demand for opium. This dual effect was regarded as an opportunity by the Turkish political elites. The solution of the “opium problem,” which continued for almost a decade resulting in many economic and political tensions was found in the weakening the hegemony of the control-supporting approaches and in the abandonment of the restrictions to a great extent. This thesis examines the opium problem in the specified era from the positions of both the Republican governing elites and the opium peasantry. The different approaches to the opium problem led to tensions and rifts among the Republican governing elite. The difference brought out mainly between the ones demanding to procure the necessary revenue for the young Republic from opium and the ones supporting to control opium under the hegemony of medicine, as a part of the world-wide discourse. The latter group was politically influential especially in the post-law period, while the former approach gained more power with the start of the war. For the opium peasantry, the new system arising from the laws led many kinds of problems, and caused the worsening of the economic and social conditions of the peasantry. Many aspects of this negative picture were the targets of the peasantry’s political reactions, resistances, and demands. These reactions were taken into account by the governing elite, and affected the course of governmental practices.
Keywords: Opium.; Opium trade -- Turkey.